Local Deuteration Enables NMR Observation of Methyl Groups in Proteins from Eukaryotic and Cell‐Free Expression Systems. Issue 25 (6th May 2021) - Dubey, Abhinav; Stoyanov, Nikolay; Viennet, Thibault; Chhabra, Sandeep; Elter, Shantha; Borggräfe, Jan; Viegas, Aldino; Nowak, Radosław P.; Burdzhiev, Nikola; Petrov, Ognyan; Fischer, Eric S.; Etzkorn, Manuel; et al.
Abstract: Therapeutically relevant proteins such as GPCRs, antibodies and kinases face clear limitations in NMR studies due to the challenges in site‐specific isotope labeling and deuteration in eukaryotic expression systems. Here we describe an efficient and simple method to observe the methyl groups of leucine residues in proteins expressed in bacterial, eukaryotic or cell‐free expression systems without modification of the expression protocol. The method relies on simple stereo‐selective 13 C‐labeling and deuteration of leucine that alleviates the need for additional deuteration of the protein. The spectroscopic benefits of "local" deuteration are examined in detail through Forbidden Coherence Transfer (FCT) experiments and simulations. The utility of this labeling method is demonstrated in the cell‐free synthesis of bacteriorhodopsin and in the insect‐cell expression of the RRM2 domain of human RBM39. Abstract : Methyl‐based magnetization usage can strongly benefit investigations of large protein systems via NMR spectroscopy. Here, a simple and cost‐effective method to obtain locally deuterated leucine suitable for methyl NMR and to quantify its benefits is presented. The approach substantially expands the applicability of methyl labeling in emerging expression systems including cell‐free and eukaryotic systems.